Perspektif Epidemiologi Sebagai Upaya Pencegahan Penyakit Tidak Menular Bagi Masyarakat Pulau Bromsi - Istyanto, Febry; Aswar, Sophian; Dori , Yahya Saul Karel; Tifen, Dian Dwiranti Patricia; Rore, Philips Roly; Lestari, Novi Ayu; Permatasari, Reforma (Penerbit Goodwood, 2025)
Purpose: This community service initiative on the impact of physical exercise on community health in Bromsi Island, Biak Numfor Regency, focuses on the prevention of non-communicable diseases (NCDs) and improving overall quality of life through structured exercise activities. Methodology/approach: The community service program consisted of (1) surveys and discussions with educators, staff, and students; (2) obtaining permits from local authorities; (3) socializing the importance of exercise; (4) presenting the health benefits of exercise; (5) organizing group exercise sessions; and (6) monitoring and evaluating the impact on the community. Results/findings: The program increased public awareness of physical activity, promoted healthy lifestyles, and decreased NCD cases, positively affecting the local economy and community productivity. Conclusion: From an epidemiological perspective, regular physical activity has been shown to help prevent non-communicable diseases in the community of Bromsi Island. Limitations: Challenges include inadequate sports facilities and limited local support. The effectiveness of these programs varied according to community participation. Contribution: This study offers insights for evidence-based health policies and highlights the need to integrate health education with physical activity to enhance community well-being. These findings can guide the promotion of exercise as a preventive strategy against NCDs, fostering a supportive environment for healthy lifestyles.